LIVING QUR'AN STUDY: READING SELECTED VERSES ASTHEMATIC ACTUAL CURRICULUM AT AL-WAFA IslamicBoarding School CIBIRU BANDUNG - Widia Duwi Putri (Islamic Studies Journal (ISLAM), 2024)
Al-Wafa Islamic Boarding School has a unique tradition, namely therecitation of selected verses which is carried out every Saturday morning. In contrast tomost Islamic Boarding Schools in general that traditionalize the reading of verses such asAyatul Khirz, Al-Waqi'ah, or Al-Mulk, Al-Wafa Islamic Boarding School actually tradesthe reading of selected verses related to Aqidah and morals such as Q.S. Luqman verses 12-19. This is interesting to study to find out how the application of reading selected verses atAl-Wafa Islamic Boarding School, how the background of reading selected verses at AlWafa Islamic Boarding School, and how the santri's reception of the reading of selectedverses at Al-Wafa Islamic Boarding School. The type of this research is descriptivequalitative with the approach of exegesis, aesthetic and functional reception theory byAhmad Rafik. The results showed that the recitation of selected verses is one of theapplications of the Thematic Actual Curriculum and is perceived exegetically which isreflected when students feel they have to apply what they understand from the recitation ofselected verses in everyday life, aesthetically which is reflected when students feel that thereis a beauty of conformity between the laws and values in the Quran and the reality ofeveryday life, and functionally reflected when students feel much calmer, peaceful, happy,and add to the treasure of knowledge when they follow the tradition of reciting selectedverses